Thermal Decomposition Investigation of Zn4O(NH2-BDC)3 (IRMOF-3) and NH2-BDC by in situ DRIFTS - Zhang, Fang; Chen, Chao; Xu, Li; Zhang, Ning (Asian Journal of Chemistry, 2012)
The thermal decomposition of a porous amino metal-organic framework, Zn4O(NH2-BDC)3 (IRMOF-3), has been investigated comparatively by in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) and TG techniques. FT-IR, PXRD, N2 adsorption-desorption and elemental analyses were applied to confirm the compositions of products. As revealed by these analyses, the ligand in IRMOF-3 exhibits different thermal decomposition behaviour than does the free ligand. Possible decomposition pathways are proposed. In addition, mesoporous carbon possessing a high BET surface area was obtained from thermal decomposition of IRMOF-3 at 800 ºC.